Mechanical Properties and Failure Modes of Rock Specimens with Specific Joint Geometries in Triaxial Unloading Compressive Test - Guoyong Duan; Jianlin Li; Jingyu Zhang; Eleyas Assefa; Xushu Sun (Advances in Materials Science and Engineering)
The effects of disconnected joints on the mechanical characteristics of rock masses are interesting and challenging aspects of rock mechanics. The prime objective of this study is to investigate the effect of joint orientations and joint connectivity rates on the strength, deformation, and failure mechanisms of rock specimens under unloading condition. To establish the relationships between different factors (confining pressure, joint orientation, and joint connectivity) and failure mechanisms, a series of triaxial unloading tests were performed. The results showed that the joint orientation had a more considerable effect than the joint connectivity on the strength and deformation of the specimens. Generally, three different types of failures were observed (i.e., shear, mixed, and split). Finally, Griffith’s theory was utilized to analyze the maximum tensile stress around the crack. The findings of this paper can also be used for practical engineering problems.